2016
DOI: 10.1016/j.tcm.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Remote monitoring of cardiac implantable electronic devices (CIED)

Abstract: With increasing indications and access to cardiac implantable electronic devices (CIEDs) worldwide, the number of patients needing CIED follow up continues to rise. In parallel, the technology available for managing these devices has advanced considerably. In this setting, remote monitoring (RM) has emerged as a complement to routine in-office care. Rigorous studies, randomized and otherwise, have demonstrated advantages to CIED patient management systems which incorporates RM resulting in authoritative guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 51 publications
(74 reference statements)
0
25
0
Order By: Relevance
“…Noteworthy is that patients with a pacemaker present were significantly less likely to have a dose adjustment, and more likely to successfully initiate sotalol than those without, perhaps due to less bradycardia, which was a key reason for failure of initiation. Given the continued advances in remote monitoring of cardiac implantable devices 27, 28 , as well as development of wearable/portable devices for measuring QT interval 29, 30 , it seems that our findings support the possibility that these patients could undergo outpatient initiation of sotalol, although more work is clearly needed.…”
Section: Discussionmentioning
confidence: 63%
“…Noteworthy is that patients with a pacemaker present were significantly less likely to have a dose adjustment, and more likely to successfully initiate sotalol than those without, perhaps due to less bradycardia, which was a key reason for failure of initiation. Given the continued advances in remote monitoring of cardiac implantable devices 27, 28 , as well as development of wearable/portable devices for measuring QT interval 29, 30 , it seems that our findings support the possibility that these patients could undergo outpatient initiation of sotalol, although more work is clearly needed.…”
Section: Discussionmentioning
confidence: 63%
“…That means you may not need to go to the clinic as often for routine device follow‐up appointments. Problems with your cardiac device or abnormal heart rhythms may be detected earlier and allow your healthcare team to respond faster by adjusting your medications or treatment plan, as needed Remote monitoring, if used correctly, may reduce the occurrence of inappropriate ICD shocks or the need for hospitalization, and may improve device function and quality of life . Additionally, some research studies have shown that remote monitoring may improve survival but other studies have not found a survival benefit …”
Section: Benefits and Challenges Of Remote Monitoringmentioning
confidence: 99%
“…3,4 • Remote monitoring, if used correctly, may reduce the occurrence of inappropriate ICD shocks or the need for hospitalization, and may improve device function and quality of life. [5][6][7][8] Additionally,…”
Section: Benefits and Challenges Of Remote Monitoringmentioning
confidence: 99%
“…In [10], 21% of health remote monitoring patients are not willing to use the system device. Redundant wiring is one of the reasons in [2] as it leads to obstruction of mobility, hazard and discomfort for the babies.…”
Section: Introductionmentioning
confidence: 99%
“…Redundant wiring is one of the reasons in [2] as it leads to obstruction of mobility, hazard and discomfort for the babies. While in [10,11], the efficiency of the device also needs to be considered and has yet to be analysed. Lower cost devices [12] that are more compact and [11] and have low power consumption for ease of mobility are preferred.…”
Section: Introductionmentioning
confidence: 99%